Wild Yankees : The Struggle for Independence along Pennsylvania's Revolutionary Frontier - Moyer, Paul Benjamin, 1970- (Book collections on Project MUSE., 2007)
Northeast Pennsylvania's Wyoming Valley was truly a dark and bloody ground, the site of murders, massacres, and pitched battles. The valley's turbulent history was the product of a bitter contest over property and power known as the Wyoming controversy. This dispute, which raged between the mid-eighteenth and early-nineteenth centuries, intersected with conflicts between whites and native peoples over land, a jurisdictional contest between Pennsylvania and Connecticut, violent contention over property among settlers and land speculators, and the social tumult of the American Revolution. In its later stages, the controversy pitted Pennsylvania and its settlers and speculators against "Wild Yankees"-frontier insurgents from New England who contested the state's authority and soil rights.In Wild Yankees, Paul B. Moyer argues that a struggle for personal independence waged by thousands of ordinary settlers lay at the root of conflict in northeast Pennsylvania and across the revolutionary-era frontier. The concept and pursuit of independence was not limited to actual war or high politics; it also resonated with ordinary people, such as the Wild Yankees, who pursued their own struggles for autonomy. This battle for independence drew settlers into contention with native peoples, wealthy speculators, governments, and each other over land, the shape of America's postindependence social order, and the meaning of the Revolution. With vivid descriptions of the various levels of this conflict, Moyer shows that the Wyoming controversy illuminates settlement, the daily lives of settlers, and agrarian unrest along the early American frontier.